2001
DOI: 10.1161/hc3301.095286
|View full text |Cite|
|
Sign up to set email alerts
|

Circulating Matrix Metalloproteinases and Their Inhibitors in Patients with Kawasaki Disease

Abstract: Background-Accelerated matrix breakdown caused by the increased activity of matrix metalloproteinases (MMPs) and/or the quantitative imbalance between MMP and tissue inhibitor of MMP (TIMP) have been implicated in several pathological conditions. MMP and TIMP may also be involved in the destruction of the coronary arterial wall and the resultant coronary arterial lesions in Kawasaki disease. Methods and Results-Plasma levels of MMPs, neutrophil elastase, and TIMPs were measured by enzyme-linked immunoassay in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
63
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 13 publications
6
63
2
Order By: Relevance
“…But despite the fact that MMP-9 levels were elevated in affected hearts in our murine model of KD, there was no correlation between circulating MMP-9 levels and enzymatic activity in affected coronary arteries (25). This is in accordance with data from cases of fatal KD, which show MMP-9 expression specifically localized to the site of coronary artery lesions (26), and the conflicting reports regarding circulating MMP-9 levels in affected children (22)(23)(24)(25). Degradation of elastin is one of the hallmarks of aneurysm formation.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…But despite the fact that MMP-9 levels were elevated in affected hearts in our murine model of KD, there was no correlation between circulating MMP-9 levels and enzymatic activity in affected coronary arteries (25). This is in accordance with data from cases of fatal KD, which show MMP-9 expression specifically localized to the site of coronary artery lesions (26), and the conflicting reports regarding circulating MMP-9 levels in affected children (22)(23)(24)(25). Degradation of elastin is one of the hallmarks of aneurysm formation.…”
Section: Discussionsupporting
confidence: 86%
“…MMP-9 may have a role in coronary artery aneurysm formation in KD. Despite conflicting data on serum levels of MMP-9 during the acute phase of KD (22)(23)(24)(25), local MMP-9 expression at the site of coronary artery aneurysms in children with KD has been documented (26). Circulating levels of molecules known to act locally may not be useful biomarkers of disease; this is especially relevant to enzymatic activity, which is tightly regulated at multiple levels including the local tissue environment (25).…”
mentioning
confidence: 99%
“…The plasma levels of neutrophil elastase and myeloperoxidase (MPO) were reported to be increased in the acute phase of KD [11]. Furthermore, the plasma levels of neutrophil elastase were reported to be higher in patients with CAL than in those without CAL [19]. Biezeveld et al reported that the plasma levels of neutrophil elastase remained high from the acute phase of KD throughout the convalescent phase (three months after the onset), suggesting that neutrophil activation may be sustained for longer than was previously assumed [20].…”
Section: The Increased Number Of Neutrophils and The Morphological Chmentioning
confidence: 99%
“…Cardiac myocyte hypertrophy occurs during developmental growth of the heart (1) and is induced in response to exercise or pathological conditions (1)(2)(3). Conversely, the heart can undergo reduction in size in response to starvation, as observed in patients with anorexia nervosa (4,5), or with decreased work load, as occurs with implantation of left ventricular assist device (6,7). Therefore, multiple stimuli can affect heart size, and maintenance of proper cardiomyocyte size is critical for normal cardiac function.…”
mentioning
confidence: 99%